2020
DOI: 10.3126/jnspoi.v4i1.30898
|View full text |Cite
|
Sign up to set email alerts
|

Dental Neglect Score and its Association with Oral Hygiene and Dental Caries among Adults visiting A Tertiary Hospital in Kathmandu

Abstract: Introduction: Dental neglect is a harmful behavior which brings many unwanted consequences in oral health. It has been found to be related to poor oral hygiene and increase in oral diseases. Dental neglect scale is a valid measure to record dental neglect among adults. Objective: To assess dental negligence using Dental Neglect Scale (DNS) questionnaire and assess its association with oral hygiene status and dental caries. Methods: Study consisted of convenient sample of 287 adults visiting Kantipu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Studies have demonstrated the association of high scores of DNS with the severity of tooth decay, missing teeth [ 14 , 15 , 16 ], few visits to the dentist [ 8 , 14 , 17 ], and the unsatisfactory assessment regarding one’s own dental health [ 6 ]. The average scores of the scale differ depending on how educated the population is: from 10.18 in the case of Indian teenagers [ 9 ] and 13.20 ± 3.80 in the case of American teenagers [ 8 ] to 15.61 ± 2.40 in the case of educated young Nepalese population [ 18 ] and 19.71 ± 3.94 in the case of young educated Indians [ 13 ].…”
Section: Dental Neglect Scalementioning
confidence: 99%
“…Studies have demonstrated the association of high scores of DNS with the severity of tooth decay, missing teeth [ 14 , 15 , 16 ], few visits to the dentist [ 8 , 14 , 17 ], and the unsatisfactory assessment regarding one’s own dental health [ 6 ]. The average scores of the scale differ depending on how educated the population is: from 10.18 in the case of Indian teenagers [ 9 ] and 13.20 ± 3.80 in the case of American teenagers [ 8 ] to 15.61 ± 2.40 in the case of educated young Nepalese population [ 18 ] and 19.71 ± 3.94 in the case of young educated Indians [ 13 ].…”
Section: Dental Neglect Scalementioning
confidence: 99%